Steroid versus steroid plus ozone during posterior epiduroscopy in the treatment of lumbar herniated disc: results of a 1-year follow-up study - Derya Bayram; Dostali Aliyev; İbrahim Aşık (BMC Anesthesiology)
Abstract Background Ozone has recently been employed in the treatment of low back pain which is a prevalent cause of disability in the population. The objective of this study was to evaluate the effects of the steroids alone or steroids plus ozone during epiduroscopy for chronic low back and radicular lower extremity pain. Methods The files of 76 individuals with chronic lumbar and lower extremity pain who had undergone posterior epiduroscopy were analyzed. One group applied steroids and standard treatment with saline for mechanical disintegration of scarring tissue in the epidural area. Other patients were injected with ozone and steroids in addition to standard treatment. Oswestry Disability Index (ODI) and Visual Analogue Scale (VAS) scores were performed before and following the intervention, at the 1st, 3rd, 6th, and 12th months. The degree of epidural scar tissue was also recorded during epiduroscopy. The classification of pain as either neuropathic or non-neuropathic was determined by the DN4 (Douleur Neuropathique 4) questionnaire. Results of the Patients Satisfaction Scale were noted in the 12th month. Pre- and post-procedure analgesic use and complications were recorded. Results There were 35 and 41 patients in the steroid alone and steroid plus ozone groups, respectively. Patient characteristics were similar, and both treatment groups showed significant differences in mean VAS and ODI scores compared to baseline (p˂0.001). However, the reduction in VAS scores was more significant in the ozone-added patients. The mean disability scores were comparable for the two groups at all follow-up points. Neuropathic pain was present in 42.9% of patients in the steroid-alone group and 34.1% in the combination group and, on follow-up 11 and 25 patients discontinued medication. The findings revealed the presence of moderate to severe fibrous tissue in 94.3% and 80.5% of the patients, respectively. Satisfied/very satisfied with the procedure was reported by 71% of subjects in the steroid-alone group and 92% of subjects in the steroid-plus-ozone group. Conclusion The combination of epidural ozone with steroids may be a viable option for the management of persistent lumbar and radicular limb pain. For individuals with lumbar herniated discs, this modality has been demonstrated to be both safe and efficacious. Clinical trial number Not applicable (Retrospective Study).